The relationship between empowering leadership and radical creativity - Yin, Wenjun; Liu, Su (Frontiers in Psychology, 2022)
Drawing on the conservation of resource theory, we theorized and tested a serial mediation model linking empowering leadership with employee radical creativity through job control and willingness to take risks. We tested our hypotheses using data collected from a time-lagged and multisource survey of 385 employees in 84 research and development teams from 20 different companies. The results demonstrated that empowering leadership had a positive indirect effect on employee radical creativity via job control and willingness to take risks, and the error management climate was found to strengthen this indirect effect. Theoretical and practical implications are also provided in the discussion section.